ANALYSIS OF THE EFFECT OF ADDING GLASS POWDER WASTE AS A CEMENT SUBSTITUTION AND THE USE OF PUMICE AGGREGATE ON THE COMPRESSIVE STRENGTH OF LIGHT CONCRETE - Galing Wira Buana; Nuni Khoirinnisa Hudaya Taher; Tira Roesdiana (Yayasan Adra Karima Hubbi, 2025)
Along with the increasing need for building materials and high cement prices, innovation in the use of alternative materials that are environmentally friendly and economical is needed. Glass powder waste, which is difficult to decompose and has the potential to pollute the environment, has the potential as a cement substitute because of its supportive physical and chemical properties. Additionally, pumice, as a lightweight aggregate, can reduce the dead load of the structure and enhance the efficiency of construction execution. This study aims to analyze the effect of the addition of glass powder waste as a cement substitution and the use of pumice aggregate on the compressive strength of light concrete. Glass waste, which comes from industrial and household waste, is used as a cement substitute with variations of 0%, 5%, 10%, and 15%. In contrast, pumice is used as a partial substitute for coarse aggregate. The method used is experimental, with laboratory testing including compressive strength tests at 14 and 28 days of age. The results showed that the addition of glass powder at a percentage of 5% gave the highest compressive strength values of 10.98 MPa (14 days) and 12.40 MPa (28 days), compared to concrete without glass powder, which only reached 8.14 MPa (14 days) and 11.11 MPa (28 days). This suggests that the combination of glass powder and pumice stone can significantly increase the compressive strength of light concrete, although the efficiency of the mixture decreases at higher percentages. This research provides an alternative to the use of local waste and aggregates in the development of environmentally friendly and economically efficient concrete.